(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the implementation of diagnostic assessment in identifying mathematics learning difficulties among elementary school students. The study used a literature review method by analyzing 10 scientific articles published between 2016 and 2026 obtained from Google Scholar. Data were analyzed through data reduction, classification, content analysis, and synthesis of findings. The results show that diagnostic assessment is effective in mapping students’ cognitive abilities into high, medium, and low categories and identifying learning errors through the Newman Error Analysis approach. In addition, diagnostic assessment can reveal non-cognitive barriers such as mathematics anxiety and low learning motivation. Follow-up strategies through differentiated instruction, concrete learning media, and the Teaching at the Right Level (TaRL) approach were found to improve students’ mathematics learning outcomes. The study concludes that diagnostic assessment plays an important role in supporting adaptive and student-centered mathematics learning. Therefore, strengthening teachers’ competencies in designing comprehensive diagnostic instruments is highly recommended.